Role of Women Entrepreneurs in Indian Economy: A Perspective - Chauhan, Babli (Journal of Commerce and Trade, 2020)
In this age of globalization, digitalization and start up, India is clearly seeing a revolution not only in economic growth but also in women Entrepreneurship. The sixth economic census released by “Ministry of statistics and programme implementation” highlights that women constitute around 14% of the total entrepreneurship in India. Today’s women entrepreneurs do not come only from the established business families or from the higher income section of the population, they come from every walk of life and from every part of the country. From running sports firms, media firms to construction companies and security and detective agencies, women are dabbling into fields that have traditionally been based of male domination. In present time, above 58% women entrepreneurs star up their business between the age of 20 to 30 year. Now, women entrepreneurs have started plunging into industry also and running their enterprises successfully. This way women is playing an important role in development of Indian economy. The prime objective of this article is to evaluate the present status of women entrepreneurs in Indian economy. Classification- JEL: M12, J28